Crystal‐Growth‐Dominated Fabrication of Metal–Organic Frameworks with Orderly Distributed Hierarchical Porosity. Issue 6 (20th December 2019) - Li, Hang; Meng, Fanchen; Zhang, Suoying; Wang, Liguang; Li, Matthew; Ma, Lu; Zhang, Weina; Zhang, Wenlei; Yang, Zhuhong; Wu, Tianpin; Lee, Sungsik; Huo, Fengwei; et al.
Abstract: Constructing architectures with hierarchical porosity has been widely considered as the most efficient way to bypass the problems related to slow mass transfer and inaccessibility of internal space in MOFs. Now, a crystal‐growth‐dominated strategy is proposed to fabricate hierarchically porous MOFs (HP‐MOFs). When the crystal growth is dominated by the monomer attachment, the aggregation of nonionic surfactant or polymer can be easily captured and released during the crystal growth process, resulting in the formation and ordering hierarchical pores along the radial direction. Owing to the accelerated mass diffusion and more exposed active sites of this design, HP‐MOFs exhibited an enhanced catalytic efficiency in styrene oxidation. Abstract : HP‐MOFs : A crystal‐growth‐dominated synthetic strategy is proposed to achieve hierarchically porous metal–organic frameworks. The HP‐MOFs have a wide pore size distribution and an orderly distributed porosity in the radial direction. Benefitting from the hierarchical architecture, HP‐MOFs exhibit enhanced catalytic efficiency in styrene oxidation.